Fatores globais e locais na determinaç\~ao do fluxo de capital para economias emergentes - Ajax Moreira; Katia Rocha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The study analyses, through a panel data model, the determinants of the net capital flow (the net sum of direct investment, portfolio investment, financial derivatives and other investment) and its volatility for a group of nineteen emerging economies in the period of 1980-2011 and suggests a methodology to evaluate the relative importance of push and pull factors. The economies analyzed (Argentina, Brazil, Bulgaria, Chile, Colombia, Hungary, India, Indonesia, Malaysia, Mexico, Peru, Philippines, Poland, Russia, South Africa, Turkey, Ukraine, Uruguay and Venezuela) correspond roughly to 95% of the JPMorgan EMBIG at January 2012. The results support economic stability represented by higher economic growth and lower inflation volatility, increase of fiscal austerity, higher governance indicators and increase of capital liberalization. The model explains up to 40% of the variance and volatility of net capital flow to the emerging economies. The importance of push factors as determinant of the variance of capital flow is lower in the recent period where pull factors become more relevant. Nevertheless, push factors, which are outside policy maker's control, explain most of the fluctuations relative to the volatility of capital flow to emerging economies. Results are robust to a set of different methodology to define capital flow crises periods.
Keywords: F01; F20; F32; 330; capital flow; emerging economies; financial crisis